MULTI-ORGAN DYSFUNCTION SECONDARY TO YELLOW SCORPION STING - Khan, Muhammad Faisal; Ullah, Hameed (Journal of Ayub Medical College Abbottabad, 2017)
Scorpion stings are common in tropical and subtropical regions. The history and clinical manifestation warrant urgent recognition and treatment. The incidence of scorpion stings in Pakistan is not known as there is no published data available in literature. We report our experience of a yellow scorpion sting victim who required intensive care admission after developing multi-organ dysfunction. Keywords: Multi-organ dysfunction; Scorpion sting; ICU; Renal replacement